1991
DOI: 10.1016/0304-3959(91)90220-r
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pre-incisional infiltration of tonsils with bupivacaine on the pain following tonsillectomy under general anesthesia

Abstract: The aim of the present study was to test the hypothesis that blockade of nociceptive input with bupivacaine during tonsillectomy can decrease pain beyond the immediate postoperative period. Fourteen patients between the ages of 6 and 18 years scheduled for tonsillectomy (with or without adenoidectomy) were randomly divided into two groups. The patients of both groups received 0.006 mg/kg atropine and anesthesia was induced by inhalation of halothane. Atracurium 0.5 mg/kg was used for myorelaxation. After oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(95 citation statements)
references
References 11 publications
2
90
0
3
Order By: Relevance
“…Some studies report that protecting the nervous system from the noxious insults of surgery, using regional analgesic techniques, results in blunting of the neuroendocrine response and reduces postoperative pain. [16][17][18][19] Raja et alused epidural anesthesia, which may have reduced postoperative pain by attenuating spinal cord hyperexcitability. [20][21] Sørensen et al showed that additional local anesthesia, intra-articular bupivacaine after intra-articular lidocaine, did not improve postoperative analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report that protecting the nervous system from the noxious insults of surgery, using regional analgesic techniques, results in blunting of the neuroendocrine response and reduces postoperative pain. [16][17][18][19] Raja et alused epidural anesthesia, which may have reduced postoperative pain by attenuating spinal cord hyperexcitability. [20][21] Sørensen et al showed that additional local anesthesia, intra-articular bupivacaine after intra-articular lidocaine, did not improve postoperative analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon, known as "wind-up", is characterized by a time-dependent increase in spinal cord responsiveness to subsequent afferent input and underlies the phenomenon of secondary hyperalgesia 19 . This may explain post-operative pain reduction when C-fibre neurotransmitters release at the dorsal horn is prevented by regional anaesthetic procedures 20 .…”
Section: Fig 4 Effect Of a 1-2 ML 05% Bupivacaine Injection At The mentioning
confidence: 99%
“…Comparisons between different techniques employed for the surgical removal of tonsils, anesthetic or corticosteroid injections in the peritonsillar space, and use of antibiotics postoperatively are resources which have been used aiming to relieve pain and improve the patient's quality of life (3)(4)(5)(6)(7)(8) . Adenotonsillectomy is an easy procedure to perform from a technical point of view that brings almost immediate benefits, in relation to breathing improvement in children, in cases of palatine tonsil and adenoid hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the literature refer to intraoperative local anesthetic infiltration in the tonsillar fossae to reduce odynophagia after tonsillectomy (4)(5)(6)(7)(8) . Since the 1970s, Laser (Light Amplification by Stimulated Emission of Radiation) has been widely used in medical practice serving several purposes.…”
Section: Introductionmentioning
confidence: 99%